Wetting ability of an acetone/based etch&rinse adhesive after NaOCl-treatment - Aguilera, Fátima S. (Medicina Oral S.L., 2012)
Objectives: to evaluate the effect of sodium hypochlorite (NaOCl) treatment on surface dentin roughness (Ra) and contact angle (CA) when using Prime&Bond NT adhesive (PB NT). Study Design: Extracted human third molars were sectioned to expose flat, superficial and deep dentin surfaces. CA and Ra were measured (1) before and (2) after 35% H3PO4 etching, and (3) H3PO4 etching + 5% NaOCl treated for 2 minutes before the application of PB NT. CA was measured by the Axisymmetric Drop Shape Analysis Technique using distilled and deionized water and PB NT. Roughness was evaluated with a profilometer, twelve radial measurements were performed in each treatment surface. Data were analyzed with two-way ANOVA and Newman-Keuls multiple comparison test procedures. Results: CA values decreased after acid etching and even more after NaOCl treatment on deep dentin when water was tested. With resin, there were not differences on CA results after H3PO4 neither after NaOCl treatment, in both dentin surfaces. Etching and NaOCl treatment resulted in surface roughness increase. Conclusions: In spite of the higher roughness after NaOCl treatment on superficial and deep dentin, the use of 5% NaOCl for 2 min after dentin demineralization when PB NT was employed did not improved the wettability of dentin, probably due to nanofiller content and/or hydrogen-bonding interactions with residues of the organic matrix on collagen-depleted dentin. Key words:Sodium hypochlorite, contact angle, roughness, Prime&Bond NT, superficial dentin, deep dentin.